The role played by QCD corrections in Lepton Number Violating processes - González - Pinochet; Marcela (2023)
3 One objective of the proposal was to involved a PhD student into one of projects, in order to develop a better scientific community around our line of research. TOTAL In the context of the present project a PhD student was involved and worked under my supervision. He is the author of one of the papers we published in this period, and finally he defended his thesis the past 19/08/2022. 4 As part of the study of the role played by QCD and QED correction, one of our objectives is to study the QCD corrections to dimension-9 operators which contribute to rare pseudoscalar mesons decays which violate lepton number in two units. These kind of processes are very important in the context of neutrino nature. We propose to extract limits on WC from the experimental bound on their Branching Ratios, reported by experiments, by considering QCD corrections and explore whether QCD corrections are as relevant in this case as in neutrinoless double beta decay. PARCIAL This is an objective partially fulfilled since it is a work in progress. Otro(s) aspecto(s) que Ud. considere importante(s) en la evaluación del cumplimiento de objetivos planteados en la propuesta original o en las modificaciones autorizadas por los Consejos. RESULTS OBTAINED:For each speciﬁc goal, describe or summarize the results obtained. Relate each one towork already published and/or manuscripts submitted. In the Annex section includeadditional information deemed pertinent and relevant to the evaluation process.The maximum length for this section is 5 pages. (Arial or Verdana, fontsize 10).Goal 1 Regarding this goal, we have published a paper in European Physical JournalC [1].In this paper we derived new upper limits on the leptonic decays of ﬂavoredmesons from the experimental limits on three-body LFV leptonic decays of µand τ. We also updated the existing phenomenological limits of the unﬂavoredmesons. These limits are shown in the paper [1]We studied the eﬀective lepton-quark dimension-6 LFV operators and theirhadronization via embedding the quark ...